From Policy To Empowerment: Evaluating The Implementation Gap In Fisher Community Empowerment Programs - Dwi Herlinda; Sujianto; Febri Yuliani; Dadang Mashur (Journal of Creative Power and Ambition (JCPA), 2026)
Fisher community empowerment is a strategic agenda in the development of Indonesia’s marine and fisheries sector. However, its implementation continues to face a gap between policy and practice. This article aims to analyze the challenges of sustainable fisher empowerment by examining the linkage between policies from the national to the village level and the reality of programs in Kuala Patah Parang Village, Indragiri Hilir Regency, Riau Province. This study employs a descriptive-analytical qualitative approach based on policy document analysis, village administrative data, literature, and the implementation of fisher empowerment programs, which are examined through the perspective of empowerment evaluation. The findings indicate that although Law Number 7 of 2016 has positioned fishers as development subjects who must be protected and empowered, regulations at the provincial and regency levels remain largely administrative-fiscal in orientation and have not translated the vision of empowerment substantively. At the village level, the implemented programs remain fragmented, output-oriented, top-down, and characterized by limited post-training assistance; consequently, they have not been able to foster the economic independence of fishers, even though approximately 80 percent of the population depends on the fisheries sector. This article argues that this gap is caused by the lack of integration between conventional administrative evaluation and participatory evaluation that positions fishers as active subjects. Therefore, an integrative evaluation model is needed, one that combines public policy effectiveness with the principles of empowerment evaluation in order to realize sustainable and independent fisher empowerment.